Coordinated activation of cellulose and repression of lignin biosynthesis pathways in rice - Ambavaram, Madana M.R.; Krishnan, Arjun; Trijatmiko, Kurniawan R.; Pereira, Andy (Oxford University Press, 2011)
Cellulose from plant biomass is the largest renewable energy resource of carbon fixed from the atmosphere, which can be converted into fermentable sugars for production into ethanol. However, the cellulose present as lignocellulosic biomass is embedded in a hemicellulose and lignin matrix from which it needs to be extracted for efficient processing. Here, we show that expression of an Arabidopsis (Arabidopsis thaliana) transcription factor, SHINE (SHN), in rice (Oryza sativa), a model for the grasses, causes a 34% increase in cellulose and a 45% reduction in lignin content. The rice AtSHN lines also exhibit an altered lignin composition correlated with improved digestibility, with no compromise in plant strength and performance. Using a detailed systems-level analysis of global gene expression in rice, we reveal the SHN regulatory network coordinating down-regulation of lignin biosynthesis and up-regulation of cellulose and other cell wall biosynthesis pathway genes. The results thus support the development of nonfood crops and crop wastes with increased cellulose and low lignin with good agronomic performance that could improve the economic viability of lignocellulosic crop utilization for biofuels.